EKLESIOLOGI KATOLIK: TANTANGAN DAN PELUANG DALAM ERA DIGITAL - Tio, Teodorus (Lembaga Penelitian STKIP Widya Yuwana, 2025)
The purpose of this study is to explore the ecclesiological challenges facing the Catholic Church in the digital age and to identify opportunities that can be utilized to strengthen the Church’s mission. The background of this study is the need to understand how the Catholic Church can navigate the complexities of the digital age while remaining faithful to its teaching and tradition. This study uses a qualitative approach with theological analysis methods, including a literature review and analysis of the Church’s magisterial documents. The discussion reveals that the main challenges facing the Church include the fragmentation of communion due to virtual interactions, the reduction of sacramental experiences in the digital context, and the risks to the Church’s authority amidst the uncontrolled spread of information. The results of the study suggest that the Catholic Church needs to develop integrative and adaptive strategies that balance the use of digital technologies with the preservation of the core values ​​of Catholic ecclesiology.